The House of Pitsligo - McKean, Charles (Proceedings of the Society of Antiquaries of Scotland, 1992)
Outlines the background to the commissioning of a model of the `castle' or House of Pitsligo, Buchan, as it was in the mid seventeenth century the assumptions made in the reconstruction of the dilapidated ruin, and how those assumptions were tested. The investigation revealed the need to re-evaluate the architecture of the period, whose quality has been underestimated.